Avaliação de fumonisinas produzidas por Fusarium verticillioides em genótipos de milho cultivados em diferentes ambientes - Rosa Júnior, Oelton Ferreira (Universidade Federal do Tocantins, 2018)
The corn crop is responsible for 40% of the grains produced in the country, being considered one of the most important segments for the Brazilian agribusiness economy. Due to its high nutritional value, maize is highly susceptible to fungus growth, especially Fusarium verticillioides, which besides causing damage to the roots, stalks and ears, is responsible for producing fumonisins, a group of thermostable mycotoxins and possibly carcinogenic, to man and animals. It is known that despite the importance, there is not much information associating the influence of different factors on its production, mainly in Brazilian tropical conditions. Studies were carried out with the general objective of evaluating the influence of environmental factors, genotypes and methods of inoculation of F. verticillioides on the severity of ear rot, seed quality, maize productivity, fumonisin production and histopathology in broilers. The investigations reported here were divided into four chapters. In the first chapter we evaluated the effect of environmental factors, genotypes and methods of inoculation of F. verticillioides on the production of fumonisins in corn grains. In the second chapter, was compared in different locations, methods of artificial (spray and injectable) and natural inoculation of F. verticillioides in ten maize genotypes by quantification of disease severity and productivity. In the third chapter a population of F. verticillioides was carried out through sanitary analysis and transmission of the fungus from plants to the seeds and from seeds to the seedlings inoculated with different methods of inoculation. Finally, the fourth chapter evaluated the harvest of 2015/2016 coming from crops containing commercial hybrids corn inoculated with F. verticillioides and the zootechnical and histopathological parameters were determined in broilers. The experimental design for the first and second chapters, conducted in the field, was also performed in the four localities studied, being a randomized block design in a 10x3 factorial scheme, with three replications, being ten maize genotypes and three inoculation methods. In the third chapter the experiments had a completely randomized design, in a 10x3 factorial scheme with four replications, being ten maize genotypes and three inoculation methods. Were used seeds from the hybrids that were inoculated by the three methods of inoculation. Each replicate consisted of a Gerbox containing 25 seeds. In the fourth chapter, the experiment was conducted in the experimental aviary of the School of Veterinary Medicine and Animal Science of the Federal University of Tocantins, on the campus of Araguaína-TO. A total of 160 broilers of Cobb 500 lineage (of one day old), were used in a completely randomized experimental design with two treatments (basal corn meal with no fumonisin and corn grain feed with fumonisin), with 10 replicates containing 8 broiler chicks each. All fumonisin concentration analyzes were performed at the Laboratory of Mycotoxology (LAMIC), Federal University of Santa Maria (UFSM), and the quantitative methodology called LC-MS / MS (Liquid Chromatography Mass Spectrometry) POP 45 was used. Regarding the results obtained, for the first chapter, it was concluded that it was not possible to assure that symptomatic and asymptomatic grains for Fusarium verticillioides infection are free from fumonisin contamination and the methods of inoculation by spraying and inoculation in the center of the ear did not influence different concentrations of fumonisins. Fumonisin production in maize grains is potentiated by high temperature environmental conditions and the susceptibility of the genotype and high severity of F. verticillioides. Under these conditions, there was a tendency to produce higher levels of fumonisins for most genotypes evaluated. The grain yield was reduced by the incidence of F. verticillioides. For the second chapter, it was verified that the method of artificial inoculation by sprinkling in the style-stigma and the injectable in the center of the spike, provided a greater intensity of the rot of the ear, allowing to differentiate of the natural method. In Planaltina, it was verified that the spray inoculation method resulted in a greater severity of the disease, caused by F. verticillioides than the injectable inoculation method in the center of the spike. Hybrids of maize P4285, DKB390PRO2 and DKB310PRO2 were the most resistant to ear rot in the four environments, while the hybrid 32R48YH showed the highest severity of the disease. The artificial inoculation method was the most efficient in mild climate environments and this information may be important in the standardization of the method for selection and characterization of maize genotypes in breeding programs. For the third chapter, it was concluded that the seeds from ears inoculated with spray presented a higher level of incidence of the pathogen, being this the most efficient method of artificial inoculation of F. verticillioides in the R1 phase for seed emergence evaluation. The hybrids 32R48YH and DKB240PRO2 had the highest level of infection by F. verticillioides because they had the highest incidence of the fungus. While the hybrids P3630H and P4285H proved to be the most resistant because they obtained the lowest incidence of the pathogen. Hybrids P3250, 32R48YH and 30K75Y presented a lower percentage of emergence when the inoculation was performed by the injectable method, while the hybrids P4285H, 30K75Y and DOW30A37PW showed a lower percentage of emergence when the inoculation was performed by the spray method. The transmission of the seed to the plant was confirmed by molecular analysis. It was found that, although the plants showed no visible symptoms, it was possible to confirm that there was a latent infection. The PCR technique was able to reveal the presence of the pathogen in maize seeds at a lower incidence level (1%). In the fourth chapter, it was concluded that the concentration of 2.78 μg/g of fumonisin determined in the diet was not sufficient to cause alterations in the zootechnical parameters (broilers weight and feed consumption) and histopathological parameters (intestinal, liver and heart tissues) of broilers of the COBB 500 lineage, fed until the 21st day. Analyzes of the zootechnical and histopathological parameters allowed to reveal minimum and safe concentrations of fumonisin that did not cause toxicological damages in broilers of Cobb 500 lineage. This is an important parameter that can contribute in the stages of production of meat and broiler chicks products.